2013
DOI: 10.1161/strokeaha.111.000217
|View full text |Cite
|
Sign up to set email alerts
|

Evidence HDAC9 Genetic Variant Associated With Ischemic Stroke Increases Risk via Promoting Carotid Atherosclerosis

Abstract: Background and purpose A novel association between a single nucleotide polymorphism (SNP) on chromosome 7p21.1 and large vessel ischaemic stroke, was recently identified. The most likely underlying gene is histone deacetylase 9 (HDAC9). The mechanism by which HDAC9 increases stroke risk is not clear; both vascular and neuronal mechanisms have been proposed. Methods We determined whether the lead SNPs were associated with asymptomatic carotid plaque (N=25179) and carotid intima-media thickness (N=31210) detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 23 publications
6
83
0
1
Order By: Relevance
“…In addition, HDAC9 is expressed in vascular cells and tissues. 49 Elevated vascular HDAC9 expression was reported to be associated with aortic and femoral atherosclerosis as well as carotid artery disease and large vessel ischemic stroke in humans. 49 Moreover, a recent genome-wide association study found two single nucleotide polymorphic (SNP) variants of HDAC9 to be strongly linked to large blood vessel disease in humans.…”
Section: Hdac9 As a Potential Therapeutic Target In Obesity: Present mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HDAC9 is expressed in vascular cells and tissues. 49 Elevated vascular HDAC9 expression was reported to be associated with aortic and femoral atherosclerosis as well as carotid artery disease and large vessel ischemic stroke in humans. 49 Moreover, a recent genome-wide association study found two single nucleotide polymorphic (SNP) variants of HDAC9 to be strongly linked to large blood vessel disease in humans.…”
Section: Hdac9 As a Potential Therapeutic Target In Obesity: Present mentioning
confidence: 99%
“…49 Elevated vascular HDAC9 expression was reported to be associated with aortic and femoral atherosclerosis as well as carotid artery disease and large vessel ischemic stroke in humans. 49 Moreover, a recent genome-wide association study found two single nucleotide polymorphic (SNP) variants of HDAC9 to be strongly linked to large blood vessel disease in humans. 50 These findings raise the intriguing possibility that therapeutically targeting HDAC9 in obesity could also favorably modulate the development of cardiovascular complications, a major cause of morbidity and mortality in this population.…”
Section: Hdac9 As a Potential Therapeutic Target In Obesity: Present mentioning
confidence: 99%
“…13 However, an effect via increasing neuronal survival might also be expected to increase risk for stroke caused by cardiac embolism as well as large artery embolism, and there was no evidence of any association between the 7p21.1 locus and cardioembolic stroke. Initial studies 14 in our laboratory have shown that HDAC9 is expressed in both intracranial and systemic large arteries, including carotid and coronary arteries. Abundant staining was found both in the endothelium and smooth muscle cells.…”
Section: Markus Wellcome Trust Genome-wide Association Study Of Ischementioning
confidence: 99%
“…39 Levels of HDAC9 mRNA expression were found to be elevated above normal levels in carotid athero sclerotic plaques compared with non diseased arterial wall. 38 Interestingly, this elevation was seen to a greater degree in carotid plaques than in athero sclerotic plaques elsewhere in the body. The reasons for this difference are unknown, although the HDAC9 variant was recently associated with coronary artery disease, 40 and it is of interest that this association was weaker than the association with large-artery stroke.…”
mentioning
confidence: 96%